(untitled) (Global Journal of Human-Social Science, 2016)
The last decade or so has seen an increasing global shift in partnership emphasis as a core to a new form of governance. For successive UK Governments partnership and other forms of inter-organisational working have become increasingly central to UK public sector managers. This paper will attempt to review the principal factors which may complicate the effectiveness of the strategy process in the context of partnership. In so doing it provides a historical review of motivation for multi-organisational partnerships, a discussion of the possible challenges in the diversity and structural dimensions and a review of the role of partnership managers.